Tissue-specific responses of Lymantria dispar L. (Lepidoptera: Erebidae) larvae from unpolluted and polluted forests to thermal stress. (February 2021) - Ilijin, Larisa; Grčić, Anja; Mrdaković, Marija; Vlahović, Milena; Filipović, Aleksandra; Matić, Dragana; Mataruga, Vesna Perić
Abstract: In this paper the effects of increased environmental temperature on the relative growth rate (RGR) and developmental time in 5th instar L. dispar larvae originating from unpolluted and polluted forests were analyzed. As indicators of the level of generated reactive oxygen species in thermal stress, we estimated midgut and hemolymph activity of the antioxidative enzymes, superoxide dismutase (SOD) and catalase (CAT), as well as the detoxifying enzymes glutathione S-transferase (GST), carboxylesterase (CaE) and acetylcholinesterase (AChE) from the midgut and brain tissue. We also examined the influence of induced thermotolerance as a species' ability to overcome the negative effects of this stressor. In larvae originating from the unpolluted forest, the midgut is the primary location of increased SOD and CAT activity and induced thermotolerance did not modified their activity in either tissue. In larvae from the polluted forest, in both tissues SOD activity was more sensitive to an increased temperature and induced thermotolerance than CAT. Carboxylesterase responded diversely to thermal stress depending on the analyzed tissue regardless the origin of larvae, while the activity of GST and AChE in tissue depended on the origin of larvae. Induced thermotolerance modified the activity of detoxifying enzymes in larvae originating from the polluted forest. Combining the selected parameters into an integrated biomarker response (IBR) the GST, CaE and AChE battery emerged as a potential biomarker for thermal stress in L. dispar larvae. Graphical abstract: Image 1 Highlights: Lymantria dispar larvae were exposed to thermal stress. Superoxide dismutase and catalase are sensitive to thermal stress. Carboxylesterase showed tissue specific responces. Glutathione S-transferases and acetylcholinesterase had origin dependent sensitivity.